Light concrete shells for parabolic trough collectors – Conceptual design, prototype and proof of accuracy. (January 2015) - Forman, P.; Müller, S.; Ahrens, M.A.; Schnell, J.; Mark, P.; Höffer, R.; Hennecke, K.; Krüger, J.
Highlights: Equivalent wind load factors for static analyses under fluctuating loads are gained. Time-dependent deformation of the concrete shell turns out insignificant. Initial deformations on micro-scale hold the main influence on the efficiency. High-strength concrete troughs can have thicknesses of a few centimetres only. Abstract: Up to now modules of parabolic trough collectors are usually made from steel frames carrying curved mirror elements. With these, the crucial disadvantage is the separation between supporting structure and reflecting surface. Here, the independent parts are merged to a very thin and light-weight but solid concrete shell having a highly precise inner surface that serves as substrate for mirror elements. Since concrete is originally very brittle and weak in tension, a special high-strength concrete with remarkable tensile strength is developed. Based on numerical analyses employing linear elastic material behaviour and limiting stresses below the tensile strength, two alternative module candidates have been designed with geometries close to already existent modules. Their design accounts for operation states by means of analytically and experimentally derived actions and constraints as well as time-dependent material effects. A first prototype on novel concrete supports demonstrates general feasibility. Highly accurate surfaces of the concrete shell, having a few centimetres of thickness only, prove structural stiffness and full optical efficiency in tests employing digital close range photogrammetry and analytically derived precision rates based on the surface slope error.